OBSERVING THE ACCESSABILITY OF DISABLED GROUPS IN MOSQUE: A CASE STUDY IN MATARAM CITY - Nazar Naamy (FiTUA: Jurnal Studi Islam, 2023)
This article tries to explain the practice of da’wah inclusion over disabled groups in houses of worship. The research using qualitative methods with a case study approach was carried out in Lombok and disability data was taken from "NTB in numbers". The data of this disability group were analyzed using Axel Honneth's theory of recognition. The study reveal that in practice da’wah inclusion there is a gap in the pattern of da’wah and the sociological reality of da’wah in Lombok, especially in Mosque. Based on data on disabilities in Lombok, it was found that out of a hundred houses of worship such as Mosques, Temples, Monasteries, and Churches, they have not been inclusive in responding to disabled groups. This can be seen from the indicators that there is no access road for people with disabilities, wheel facilities, Quran Braille, hearing aids, lack of religious references that can make it easier for people with disabilities to study religious studies independently, and sign language interpreters of lecture materials, as well as recognition in religious and social names.